Population, demographic and socioeconomic characteristics associated with state preemption laws in the United States, 2009–2018 - José A. Pagán; Diana Silver; Kelley Akiya; Jennifer L. Pomeranz (PLoS ONE, 2025)
Objective In the United States, preemption laws enacted by state governments can remove local government authority to enact policy and undermine community self-determination and local democracy. No study to date has evaluated the population, demographic, and socioeconomic characteristics associated with state preemption of public health policies. Our study identifies state characteristics associated with preemption of local paid sick leave, food and nutrition, tobacco control, and firearm safety policies. Methods We conducted a Classification and Regression Tree (CART) analysis using state-level demographic, socioeconomic, and population health indicators from 2009 to 2018 to predict state ceiling preemption of local paid sick leave, food and nutrition, tobacco control, and firearm safety policies. Results Several demographic, economic, political, and health factors best distinguish states with and without preemption in each of the four domains. Total state population was an important characteristic in all four trees and the non-Hispanic Black population was important in three trees. All other age- and race/ethnicity-related demographic variables included were important characteristics in at least one tree. Additionally, adult obesity and flu vaccination were relevant in the paid sick leave tree and firearm-deaths, suicide-deaths, and the unemployment rate were relevant in the firearm safety tree. The relationship between specific factors and preemption in each of the four domains varied depending on the location of the factor within the trees. Conclusions and relevance Specific population, demographic and economic characteristics in a state are associated with the adoption of ceiling preemption of paid sick, food and nutrition, tobacco, and firearm safety laws, but these characteristics vary by domain. Our study identified which populations within groups of states may be affected by preemption. The findings can inform whether preemption laws considered or adopted in a state may also require protective measures for population groups that could be adversely affected by these laws.